A trial bank model for the publication of clinical trials. - Sim, I. (American Medical Informatics Association, 1995)
Clinical trials constitute one of the main sources of medical knowledge, yet trial reports are difficult to find, read, and apply to clinical care. Reasons for these difficulties include the lack of a common, standardized, structure for trial reports; the restricted length of reports; and limited computer support for use of the literature. We propose a new model of reporting clinical trials, in which trials are published as both prose commentary and as data in electronic "trial banks." The prose will allow authors to discuss their trials in writing; the electronic database will allow readers easy access to well-defined data about the trials. We are developing a formal conceptual model of the clinical trials domain for integrating the use of multiple trial banks. We will then focus on validating this conceptual model with clinical literature users.